Combining analytical epidemiology and genomic surveillance to identify risk factors associated with the spread of antimicrobial resistance in Salmonella enterica subsp. enterica serovar Heidelberg. Issue 11 (23rd November 2022) - Hetman, Benjamin M.; Pearl, David L.; Barker, Dillon O. R.; Robertson, James; Nash, John H. E.; Reid-Smith, Richard; Agunos, Agnes; Carrillo, Catherine; Topp, Edward; Van Domselaar, Gary; Parmley, E. Jane; Bharat, Amrita; et al.
Abstract : Antimicrobial resistance (AMR) has become a critical threat to public health worldwide. The use of antimicrobials in food and livestock agriculture, including the production of poultry, is thought to contribute to the dissemination of antibiotic resistant bacteria (ARB) and the genes and plasmids that confer the resistant phenotype (ARG). However, the relative contribution of each of these processes to the emergence of resistant pathogens in poultry production and their potential role in the transmission of resistant pathogens in human infections, requires a deeper understanding of the dynamics of ARB and ARG in food production and the factors involved in the increased risk of transmission.